2003
DOI: 10.1002/jmri.10351
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the quantification of myocardial perfusion using an automatic spline‐based registration algorithm

Abstract: Purpose:To improve the quantification of myocardial perfusion by registering the time series of magnetic resonance (MR) images with injection of gadolinium. Materials and Methods:Eight patients underwent MR scans to perform myocardial perfusion exam. Two short axis views of the left ventricle (LV) were acquired in free breathing. Two masks for performing the spatial registration of the images were evaluated. The registration was based on pixel intensity in a multi-resolution scheme. The efficiency of this corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 17 publications
(21 reference statements)
0
39
0
Order By: Relevance
“…[5][6][7] Remaining motion artifacts may then be reduced by the use of various elastic registration procedures that warp the spatial data. [8][9][10] In cases where gating is not possible or unreliable, nongated dynamic datasets have been registered by a variety of methods and for various purposes. For instance, in nuclear medicine, noise reduction may be performed through temporal averaging of nongated signals.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Remaining motion artifacts may then be reduced by the use of various elastic registration procedures that warp the spatial data. [8][9][10] In cases where gating is not possible or unreliable, nongated dynamic datasets have been registered by a variety of methods and for various purposes. For instance, in nuclear medicine, noise reduction may be performed through temporal averaging of nongated signals.…”
Section: Introductionmentioning
confidence: 99%
“…For the data sets we used there appeared to be negligible rotation motion. Others have corrected for translational and rotational motion and used results obtained from manual registration without rotation as the gold standard (6,8). Bidaut and Vallee (6) reported that the relative motion of the anatomical landmarks at the extremities and center of the mid-wall segment is reduced compared to manual registration after correction for rotational motion is incorporated.…”
Section: Discussionmentioning
confidence: 99%
“…Gallippi et al (7) correct for motion using a statistical approach whereby an image in the temporal center of the sequence is chosen as the reference, and the images are registered using a matching metric based on intensity variations and edge directions. Dornier et al (8) minimize the mean squared difference proposed in (9) between the perfusion images within tightly cropped myocardial masks. Bracoud et al (10) use the mutual information (11) metric to register.…”
mentioning
confidence: 99%
“…Registration was then achieved through translation only. In (Dornier et al, 2003) two methods where described that would either use simple rectangular masks around the myocardium or an optimal masks, where the area with the high intensity change where eliminated as well. Rigid registration was then achieved by employing a spline-based multi-resolution scheme and optimizing the sum of squared differences.…”
Section: State Of the Artmentioning
confidence: 99%